Interactions between Roseburia intestinalis and diet modulate atherogenesis in a murine model. (December 2018) - Kasahara, Kazuyuki; Krautkramer, Kimberly; Org, Elin; Romano, Kymberleigh; Kerby, Robert; Vivas, Eugenio; Mehrabian, Margarete; Denu, John; Bäckhed, Fredrik; Lusis, Aldons; Rey, Federico
Abstract Humans with metabolic and inflammatory diseases frequently harbour lower levels of butyrate-producing bacteria in their gut. However, it is not known whether variation in the levels of these organisms is causally linked with disease development and whether diet modifies the impact of these bacteria on health. Here we show that a prominent gut-associated butyrate-producing bacterial genus (Roseburia ) is inversely correlated with atherosclerotic lesion development in a genetically diverse mouse population. We use germ-free apolipoprotein E-deficient mice colonized with synthetic microbial communities that differ in their capacity to generate butyrate to demonstrate thatRoseburia intestinalis interacts with dietary plant polysaccharides to: impact gene expression in the intestine, directing metabolism away from glycolysis and toward fatty acid utilization; lower systemic inflammation; and ameliorate atherosclerosis. Furthermore, intestinal administration of butyrate reduces endotoxaemia and atherosclerosis development. Together, our results illustrate how modifiable diet-by-microbiota interactions impact cardiovascular disease, and suggest that interventions aimed at increasing the representation of butyrate-producing bacteria may provide protection against atherosclerosis. Roseburia intestinalis is a butyrate-producing member of the gut microbiome that can use dietary plant polysaccharides to alter host metabolism, transcription and epigenetics, and lower inflammation and endotoxaemia, resulting in reduced atherosclerosis.